A study on clinical and laboratory features of pit viper envenomation from Central Kerala, India - P. T., Hijaz; C. R., Anil Kumar; John, Bins M. (International Journal of Advances in Medicine, 2018)
Background: Snakebite envenomation is an important public health problem faced by the tropical countries with India, the worst affected in terms of mortality and morbidity. In spite of increasing reports of other snake species causing envenomation, the existing research and management strategies including antivenom are still focused on the “Big Four” species- Russel’s viper, saw scaled viper, common krait and spectacled cobra. Pit vipers as a group are being increasingly reported to cause human bites from different parts of the country. Hence, we decided to study the clinico-epidemiology of pit viper bites. Methods: 30 cases of proven pit viper bites who attended our Department during the study period of 18 months were analysed for the epidemiological factors, clinical features and abnormalities in laboratory parameters. Results: Hump nosed pit viper (Hypnale hypnale) was responsible for all the thirty cases. 57% of cases were females. Mean age of victims was 41.8 years. 17 patients had exclusively local envenomation. Ten cases had coagulopathy along with local envenomation. Three patients developed acute kidney injury of whom three underwent dialysis. No mortality was observed in the study. Low fibrinogen levels were observed in all cases with coagulopathy and some had low levels of factor V (70%) and factor VIII (40%). Conclusions: Hump nosed viper bites were observed to be common in this part of the country. Significant envenomation can occur. Further epidemiologic studies involving more centres will be helpful in quantifying the true incidence of bites. Since no specific antivenom is available, further researches in this direction are warranted.